Educational disparities in adult health across U.S. states: Larger disparities reflect economic factors - Montez, Jennifer Karas; Cheng, Kent Jason (Frontiers in Public Health, 2022)
Introduction Education level is positively associated with adult health in the United States. However, new research shows that the association is stronger in some U.S. states than others, and that states with stronger associations also tend to have poorer overall levels of health. Understanding why educational disparities in health are larger in some states than others can advance knowledge of the major drivers of these disparities, between individuals and states. To that end, this study examined how key mechanisms (economic conditions, health behaviors, family, healthcare) help explain the education-health association in each state and whether they do so systematically. Methods Using data on over 1.7 million adults ages 25–64 in the 2011–2018 Behavioral Risk Factor Surveillance System, we estimated the association between education level and self-rated health in each state, net of age, sex, race/ethnicity, and calendar year. We then estimated the contribution of economic, behavioral, family, and healthcare mechanisms to the association in each state. Results The strength of the education-health association differed markedly across states and was strongest in the Midwest and South. Collectively, the mechanisms accounted for most of the association in all states, from 55% of it in North Dakota to 73% in Oklahoma. Economic (employment, income) and behavioral (smoking, obesity) mechanisms were key, but their contribution to the association differed systematically across states. In states with stronger education-health associations, economic conditions were the dominant mechanism linking education to health, but in states with weaker associations, the contribution of economic mechanisms waned and that of behavioral mechanisms rose. Discussion Meaningful reductions in educational disparities in health, and overall improvements in health, may come from prioritizing access to employment and livable income among adults without a 4-year college degree, particularly in Southern and Midwestern states.